Research on Deformation and Fracture Characteristics of the Fractured Rock Mass Under Coupling of Heavy Rainfall Infiltration and Mining Unloading - Wang, Menglai; Li, Xiaoshuang; Yang, Shun; Teng, Lin; Chen, Qiusong; Jiang, Song (Frontiers in Earth Science, 2022)
The present study used PFC numerical software to examine the mechanical properties and fracture propagation characteristics of fractured rock mass under coupling of heavy rainfall infiltration and mining-unloading based on the engineering background of the Dexing mine, the pore water pressure is set to 0 mpa, 0.5 mpa, 1.0 mpa, 1.5 mpa, 2.0 mpa, the true triaxial lateral unloading rate is 0.3 mpa/level and 0.6 mpa/level, and the water content state of rock is dry, natural and saturated respectively, then the true triaxial compression numerical simulation test is carried out, the results showed that with the increase of water content, the rock compaction stage increases, the elastic stage shortens and the yield stage becomes more obvious. The faster the unloading rate is, the greater the influence on the rock strain is. After unloading, the stress jump point appears and the strain increase rate becomes larger, the volume of the rock increased and occurs large deform in the unloading direction, finally it leads to severe brittle failure of the rock. With the increase of rock pore water pressure, the compressive strength and the peak strain of the rock decrease, and the pore water pressure accelerates the process of rock failure.